Project Report on Design and Development of a 0.5-1.5 GH low Noise Cooled Hemt Amplifier - DEEPANKAR ROY and SHARATH V B (2003)
INTERNAL GUIDE: JYOTHI DESHMUKH, MVJCE EXTERNAL GUIDE: RAGHUNATHAN A, RADIO ASTRONOMY LAB R&I
Keywords: 0.5-1.5 GH low Noise Cooled Hemt Amplifier